Canine otitis externa by pathogenic Aspergillus niger: case report - Ygreda, Gabriela (2021)
This paper reports a clinical case of Aspergillus otomycosis in an 8-year-old male English Cocker Spaniel, with a previous diagnosis of immune-mediated hemolytic anemia. The patient was treated for pain and discomfort in both ears. Routine blood tests were performed, as well as cytology and microbiological culture of ear secretion. Aspergillus niger together with Malassezia pachydermatis were the isolated, the oral and topical antifungal therapy was established with favorable results after 30 days of treatment. The isolated mold exhibited some important virulence factors such as hemolytic, lipase and amylase activity, as well as in vitro susceptibility to azole antifungals. In the immunosuppressed patients with otitis externa, it is necessary to perform microbiological cultures for environmental fungi, in addition to evaluating the pathogenic characteristic at the phenotypic level. This may help to establish a proper therapeutic approach and monitoring of liver enzymes for possible adverse effects.